Assess the Accuracy and Reliability of Advanced Ultrasound Techniques in Predicting and Managing Abnormal AFI and Mitigating Potential Fetal Outcome - Ahtasham Amjad; Madiha Iqbal; Khawaja Ruman Ahmad (Pakistan Journal of Medical & Health Sciences, 2024)
Background: This research seeks to provide a comprehensive and standardized approach to AFI assessment, comparing the accuracy and reliability of the single pocket method against the four pocket method through a rigorous validation process. Aim: To leverage cutting-edge ultrasound technologies to provide a detailed analysis of how alterations in AFI may affect fetal wel being in distinct trimesters and to compare the impact of mitigate potential fetal outcome of patients with 2nd and 3rd trimesters with abnormal amniotic fluid index (AFI) through ultrasound techniques. Methods: This comparative prospective observational study was conducted at Gilani Ultrasound Centre, University of Lahore, from 30th November 2022 to 30th December 2023. After the approval of the gynaecology department and written informed consent of the patients, the data of 200 pregnant patients of the 3rd and 4th trimesters were analyzed. Ultrasound Doppler machines were utilized for research purposes, although AFI levels were measured at 3rd and 4th trimesters of pregnancy. Increased and decreased AFI levels and fetomaternal outcomes were monitored. Results: In the single pocket method, 24 out of 100 cases exhibited abnormal Amniotic Fluid Index (AFI), with 16 cases classified as polyhydramnios and 8 cases as oligohydramnios. Conversely, in the four pocket method, 46 out of 100 cases had abnormal AFI, with 22 cases identified as polyhydramnios and 24 as oligohydramnios. The mean gestational age for the overall cohort of 200 females was 26.87. Within this group, the largest pocket volume in the single-pocket method had a mean AFI of 5.24±2.3, while the four-pocket method exhibited a mean AFI of 13.38±4.5. Results also indicated no association between foetal outcomes and abnormal AFI in patients undergoing standard ultrasonography strategies, as p-value > 0.05. Conclusion: Phelan’s and Chamberlain’s methods demonstrate noncomparable precision in assessing amniotic fluid index (AFI) during the second and third trimesters of pregnancies. The findings also suggested that there is no association between foetal outcomes and abnormal Amniotic Fluid Index (AFI) in patients who undergo Phelan’s and Chamberlain’s ultrasonography strategies. Keywords: amniotic fluid index (AFI), the largest vertical pocket (LVP), PIH, PROM